Effect of fermented liquid feed on feed efficiency, gut health and immunity of Large White Yorkshire (LWY) fattener pigs - BURAGOHAIN, R; SAIKIA, B N (The Indian Journal of Animal Sciences, 2025)
The study assessed effect of fermented liquid feed (FLF) on feed efficiency, gut health and immunity of LWY fattener pigs. Weaned piglets (24) were assigned four dietary treatments (T1, T2, T3, T4) in two phases in a randomised block design for 180 days. T1 was fed standard ration (SR), T2 was fed SR mixed with water (1:2, w/w), T3 and T4 were fed FLF fermented by Lactobacillus acidophilus (T3) and Enterococcus faecium (T4) respectively. Feed efficiency was calculated fortnightly; diarrhoea score and incidence up to day 14; faecal pH, NH3-N, lactic acid, LAB, Escherichia coli and Salmonella on day 1, 60, 120 and 180; immune responses and histomorphology of small intestine at 42nd day. Final body weight and gain, feed efficiency was significantly higher in T3 and T4. The DS and DI reduced significantly in T3 and T4. Increased faecal pH and reduced NH3-N recorded in T3 and T4 on 180th and 120th day respectively. Faecal LAB was significantly higher on 120th day and increasing trends on 60th and 108th day recorded in T3 and T4. Faecal Escherichia coli and Salmonella was significantly reduced in T3 and T4. Increased VH, decreased CD and higher AVSA with infiltration of mononuclear and lymphoid follicles observed in T3 and T4. Antibody titre (HI log10/ml) on 7th and 21st day post-inoculation was recorded significantly higher in T3 and T4. Based on findings of the study, feeding of FLF by Lactobacillus acidophilus or Enterococcus faecium was recommended to LWY fattener pigs.